2017
DOI: 10.1007/s11571-017-9454-0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous analogising caused by text stimuli in design thinking: differences between higher- and lower-creativity groups

Abstract: Understanding the cognitive processes used in creative practices is essential to design research. In this study, electroencephalography was applied to investigate the brain activations of visual designers when they responded to various types of word stimuli during design thinking. Thirty visual designers were recruited, with the top third and bottom third of the participants divided into high-creativity (HC) and low-creativity (LC) groups. The word stimuli used in this study were two short poems, adjectives wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Researchers have utilised biometric measurement to study the impact of various types of stimuli on design creativity. For instance, various brain activities and differences caused by distinct word stimuli were found between high and low creativity groups of designers based on EEG measurement [76]. Similarly, an EEG-utilising study suggested that the involvement of text in idea generation had an positive impact on design creativity and idea generation [77].…”
Section: Design Creativity and Design Fixationmentioning
confidence: 99%
“…Researchers have utilised biometric measurement to study the impact of various types of stimuli on design creativity. For instance, various brain activities and differences caused by distinct word stimuli were found between high and low creativity groups of designers based on EEG measurement [76]. Similarly, an EEG-utilising study suggested that the involvement of text in idea generation had an positive impact on design creativity and idea generation [77].…”
Section: Design Creativity and Design Fixationmentioning
confidence: 99%
“…Also, the inhibitory state can play an active (inhibitory) role in gating the transfer of information in specific neuronal pathways (Lopes da Silva, 1991). As creativity is a crucial skill of a designer, its understanding and empowerment via EEG metrics already gathered interest in the field (Jaarsveld et al, 2015;Liu et al, 2018) despite it being still at a preliminary stage. EEG variation, especially the model based on ERS/ERD, already provides different possibilities in clinical diagnosis (Pfurtscheller and Silva, 2017), decision-making prediction (Ratcliff et al, 2009), emotion detection (Lan et al, 2016) and other human-machine interface applications (Foldes and Taylor, 2013).…”
Section: Eeg-based Performance Estimationmentioning
confidence: 99%
“…Low-and high-pass filters with cutoff frequencies of 50 and 1 Hz, respectively, were applied to all signals based on finite-impulse-response filters to remove the line noise, muscle movement contamination, oculomotor activities, and direct-current drift. The 90-s EEG signals of each condition were divided into 1.6-s epochs based on previous studies Liu, Chang, Yang, & Liang, 2018;Wang, Jung, & Lin, 2015). Several epochs were rejected manually due to electrical artefacts.…”
Section: Data Analysesmentioning
confidence: 99%